Pengaruh Peran Ganda, Stres Kerja dan Motivasi Kerja terhadap Kinerja Karyawan Perempuan PT Lion Motor Indonesia - Fadhilah, Chaerunnisa Nurul; Gunawan, Ahmad (Jurnal Informatika Ekonomi Bisnis, 2024)
The purpose of this study was to determine the effect of multiple roles, work stress, and work motivation on the performance of female employees. This research uses quantitative methods. The location of this research was conducted at PT Lion Motor Indonesia. The variable measurement used in this study is using the Likert scale. The population in this study is the number of married female employees as many as 60 people. The sampling technique in this research uses the non probability sampling technique, using saturated sampling. data processing tools are used in the form of computer software, namely the SmartPLS (Partial Least Square) version 3.0 program for hypothesis testing. Analysis in this study was carried out in three ways, namely analyzing the outer model, inner model, and hypothesis testing. This study found that the Dual Role variable (X1) has no significant effect on employee performance (Y), the Work Stress variable (X2) has no significant impact on employee performance (Y), and the Work Motivation variable (Y) has a significant effect on employee performance (Y).